Deriving quantitative information from multiparametric MRI via Radiomics: Evaluation of the robustness and predictive value of radiomic features in the discrimination of low-grade versus high-grade gliomas with machine learning. (March 2023) - Ubaldi, Leonardo; Saponaro, Sara; Giuliano, Alessia; Talamonti, Cinzia; Retico, Alessandra
Highlights: A reliable feature extraction pipeline for multiparametric MRI data was described. Image preprocessing is a fundamental step in radiomic MRI analysis. A set of robust features respect to the image preprocessing technique and features extraction settings was founded. The robustness of radiomic features and the impact on their predictive power were investigated. Abstract: Purpose: Analysis pipelines based on the computation of radiomic features on medical images are widely used exploration tools across a large variety of image modalities. This study aims to define a robust processing pipeline based on Radiomics and Machine Learning (ML) to analyze multiparametric Magnetic Resonance Imaging (MRI) data to discriminate between high-grade (HGG) and low-grade (LGG) gliomas. Methods: The dataset consists of 158 multiparametric MRI of patients with brain tumor publicly available on The Cancer Imaging Archive, preprocessed by the BraTS organization committee. Three different types of image intensity normalization algorithms were applied and 107 features were extracted for each tumor region, setting the intensity values according to different discretization levels. The predictive power of radiomic features in the LGG versus HGG categorization was evaluated by using random forest classifiers. The impact of the normalization techniques and of the different settings in the image discretization was studied in terms of the classification performances. A set of MRI-reliable features was defined selecting the features extracted according to the most appropriate normalization and discretization settings. Results: The results show that using MRI-reliable features improves the performance in glioma grade classification ( AUC = 0.93 ± 0.05 ) with respect to the use of raw ( AUC = 0.88 ± 0.08 ) and robust features ( AUC = 0.83 ± 0.08 ), defined as those not depending on image normalization and intensity discretization. Conclusions: These results confirm that image normalization and intensity discretization strongly impact the performance of ML classifiers based on radiomic features. Thus, special attention should be provided in the image preprocessing step before typical radiomic and ML analysis are carried out.